Mesenchymal stem-cell-derived exosomal miR-145 inhibits atherosclerosis by targeting JAM-A - Wenzhi Yang; Ruihua Yin; Xiaoyan Zhu; Shaonan Yang; Jing Wang; Zhenfeng Zhou; Xudong Pan; Aijun Ma (Elsevier, 2021)
Atherosclerosis is a chronic inflammatory disease associated with the development of plaques that can be converted into an acute clinical event by thrombosis or plaque rupture. Mesenchymal stem cells (MSCs) exhibit therapeutic effects for the treatment of various diseases, including atherosclerosis. In this study, we show that microRNA-145 (miR-145) is associated with atherosclerosis by microRNA sequencing and bioinformatics analysis. MSC-derived miR-145-rich exosomes could efficiently deliver miR-145 from MSCs to human umbilical vein endothelial cells (HUVECs). Treatment of miR-145-rich exosomes could downregulate JAM-A, inhibit migration in vitro, and reduce atherosclerotic plaque in vivo. Our study suggests that MSC-derived miR-145-rich exosomes have great potential for atherosclerosis prevention.